Assessment of Apical Extrusion of Debris during Endodontic Retreatment with 3 Rotary Nickel-Titanium Retreatment Systems and Hand Files - Gkampesi S.; Mylona Z.; Zarra T.; Lambrianidis T. (Balkan Stomatological Society, 2016)
Aim: to evaluate the amount of debris extruded apically as well as the time needed for removal of root canal filling material using ProTaper, MTwo, REndo NiTi rotary retreatment systems and hand files.